ANALISIS KUAT TEKAN BETON MENGGUNAKAN AGREGAT HALUS PASIR PANTAI JAWAI DAN AGREGAT KASAR BATU PECAH DI KABUPATEN SAMBAS KALIMANTAN BARAT - Angga, Angga; Rizul Rachmadi, Teguh; ryanti, eva (Jurusan Teknik Sipil Polnep, 2023)
Concrete is a composite material (mixture) of several materials whose basic binder consists of a combinationof fine aggregate, coarse aggregate, water and different additives in a particular mixture. Sand is a fillermaterial that is used with a binder and water to form a dense and hard mixture. The beach sand in the JawaiDistrict, Sambas Regency has the potential because of its availability in large quantities, namely 42.53 kmlong, quite a lot of sandy beaches and rocks in the hills of Ramayadi Village. This study aims to compare and determine the value of the compressive strength of concrete produced fromconcrete using beach sand as a substitute for fine aggregate that is treated (washed and not washed) and byusing coarse aggregate in the form of crushed stone from the South Jawai District, Sambas Regency. Theresearch was conducted on cube specimens measuring 15 cm long, 15 cm wide and 15 cm high.The tests carried out were testing the compressive strength of concrete at the age of 7 days and 14 days. Thetest results at the age of 7 days for unwashed beach sand and washed beach sand respectively showed anaverage compressive strength of 114.0514 kg/cm2 and 153.9535 kg/cm2. While the test results at the age of14 days for unwashed beach sand and washed beach sand respectively showed an average compressivestrength of 142.6046 kg/cm2 and 209.8392 kg/cm2.These instructions give you guidelines for preparing papers for Jurnal Retensi. Use this document as atemplate using Microsoft Word, TNR, 10pt, single space. The electronic file of your paper will be formattedfurther at Jurnal Retensi. Abstract length is about 150-200 words, giving a brief summary of the content,reason of research, review study, and the methodology; and a brief statement about the research and its resultand prospect. Don’t include any picture, tables, elaborate equations nor references in abstract.